Pulsed Field Ablation: A Systematic Review - Poe Nu Htay; Mya Hnin Aung; Thiri May Sin; May Thet Naing Oo; Sai Say Han; Eaint Nadi Naing; Myat Soe Thet; Khin Maung Htay (Health Science Reports)
ABSTRACT Background Atrial fibrillation (AF) is the most prevalent cardiac arrhythmia, leading to significant health and economic burdens. Pulmonary vein isolation (PVI) is a key treatment strategy, with pulsed field ablation (PFA) emerging as a promising method due to its specificity and reduced collateral damage compared to traditional thermal ablation techniques like radiofrequency ablation (RFA) and cryoablation (CB). Materials and Methods A comprehensive literature search was performed across multiple databases, including PubMed, Embase, and MEDLINE via Ovid, Scopus, Cochrane CENTRAL, and ClinicalTrials.Gov. Studies reporting on the efficacy and safety of PFA in AF treatment were selected and analyzed. Quality assessment of the studies was conducted using the Newcastle–Ottawa Scale. Result Of the 440 articles initially identified, 28 met the inclusion criteria. PVI using PFA demonstrated high success rates, with most studies reporting over 90% success. Durability stands around 65% after 1 year. Mortality was 0.06%–0.32%, while stroke rate was 0.3%–4.4%. There were no reported oesophageal injuries or pulmonary vein stenosis due to the highly selective electroporation‐induced cell death caused by PFA rather than coagulative necrosis, sparing nearby structures. There is a short learning curve for PFA. Conclusion PFA is a highly effective and safe ablation method. It offers an alternative to conventional thermal ablation strategies in the treatment of AF, showing promise to reduce the risk of collateral damage and complications associated with thermal ablation techniques. However, further research is needed to understand its long‐term efficacy and safety fully and to standardize procedural protocols for wider clinical application.